The musical gift : sonic generosity in post-war Sri Lanka - Sykes, Jim, 1976- (Critical conjunctures in music & sound., 2018)
The Musical Gift tells Sri Lanka's music history as a story of giving between humans and nonhumans, and between populations defined by ethnic and religious difference. Author Jim Sykes argues that the genres we currently recognize as Sri Lanka's esteemed traditional musics were not originally about ethnic or religious identity but were gifts to gods intended to foster protection and/or healing. Noting that the currently assumed link between music and identity helped produce the narratives of ethnic difference that drove Sri Lanka's civil war (1983-2009), Sykes contends that the promotion of histories of cultural interaction, exchange, and respect for difference through musical giving has a role to play in post-war reconciliation. The Musical Gift includes a study of how NGOs used music to promote reconciliation in Sri Lanka, the first ethnography of the plight of musicians during the war in the Tamil-dominated north and of Sinhala Buddhist drummers in the south, and a theorization of the relations between musical gifts and commodities. Eschewing a strict binary between the gift and identity, Sykes claims that the world's music history is largely a story of entanglement between these paradigms. Drawing on fieldwork conducted widely across Sri Lanka over a span of eleven years, The Musical Gift brings anthropology's canonic literature on "the gift" into music studies fully for the first time, while engaging with anthropology's "ontological turn" and the "new materialism" in religious studies